Improved chicken embryo cell culture plaque assay for scrub typhus rickettsiae. - Woodman, D R (1977)
The plaque technique for three strains of Rickettsia tsutsugamushi in chicken embryo cell cultures was greatly improved by modifying the trypsinizing procedure and employing homologous chicken serum in the overlay medium.